Journal of Optometry in Emerging Sources Citation Index (ESCI) and peer-review process during COVID-19 pandemic - González-Méijome, José Manuel (2020)
[Excerpt] By March 2020, while the entire planet Earth was entering a dark time of pandemia, we communicated in this editorial the trends of J Optom in different bibliometric indices including Impact Factor, SCImago Journal Rank ing, H-index, CiteScore and Source Normalized Impact per Paper. (1) More recently the CiteScore has been reviewed by Else vier to mitigate some short-term trends and J Optom raised even further in its score from 1.65 to 2.3.2 Accord ing to Scoups, this new calculation enforces credibility of the score by only considering peer-review publications, considering a longer window of 4 years instead of 3 and considering the more recent citations in the year of calculation.3 This is only an aspect of the impact of the journal that has increased steadily as it continues to con solidate through different milestones achieved over the last years (4). [...]